The Odivelas Palaeozoic volcano-sedimentary sequence: Implications for the geology of the Ossa-Morena Southwestern border - Moreira,N. (2010)
We present a preliminary characterization of the structure, stratigraphy and petrography of a sequence including the Odivelas Limestone near Covas Ruivas locality (Ossa-Morena Zone, Évora-Beja Domain). In this area, limestone and tuffites occur spatially associated with mafic meta-volcanic rocks presenting mineral parageneses typical of low grade metamorphism (greenschists facies) and with the occasional occurrence of silica iron exhalites (jaspers). Previous work dated the limestones at this locality as latest Emsian - early mid Eifelian. As indicated by folded and brittle structures, this Devonian sequence was affected by two Variscan deformation phases, which where individualized, related with regional orogenic D2 and D3 phases. The structural data indicate that the Odivelas Limestone stratigraphically overlays the metavolcanic rocks, although de contact between them was tectonically affected by a thrusting and/or shearing. Considering age assigned to the Odivelas Limestone and the fact that the effects of the regional D1 are not visible in the studied area one can consider that, in this region, D1 is pre-latest Emsian, i.e., Lower Devonian or older.